2021
DOI: 10.1103/physrevapplied.15.044010
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Spin, Anomalous, and Planar Hall Effects in Ferromagnet–Heavy-Metal Nanostructures

Abstract: Ferromagnetic (FM)/heavy metal (HM) nanostructures can be used for the magnetic state readout in the proposed magneto-electric spin-orbit logic by locally injecting a spin-polarized current and measure the spin-to-charge conversion via the spin Hall effect. However, this local configuration is prone to spurious signals. In this work, we address spurious Hall effects that can contaminate the spin Hall signal in these FM/HM T-shaped nanostructures. The most pronounced Hall effects in our Co50Fe50/Pt nanostructur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…It is important to note that equations 11 and 12 are no longer valid if the ferromagnetic electrodes exhibit fringe or stray fields that can act on the DUT. Such fields are well known to complicate the analysis of spin measurements [23,[75][76][77][78][79] and can appear in quite different forms: 1.) As long as the width of the electrode is small enough that a single-domain magnetization prevails [42], fringe fields with relevant strengths should only be located at the electrode's two faces that are normal to the electrode's easy-axis [42,80].…”
Section: J Magnetic Field Dependent Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that equations 11 and 12 are no longer valid if the ferromagnetic electrodes exhibit fringe or stray fields that can act on the DUT. Such fields are well known to complicate the analysis of spin measurements [23,[75][76][77][78][79] and can appear in quite different forms: 1.) As long as the width of the electrode is small enough that a single-domain magnetization prevails [42], fringe fields with relevant strengths should only be located at the electrode's two faces that are normal to the electrode's easy-axis [42,80].…”
Section: J Magnetic Field Dependent Measurementsmentioning
confidence: 99%
“…As long as the width of the electrode is small enough that a single-domain magnetization prevails [42], fringe fields with relevant strengths should only be located at the electrode's two faces that are normal to the electrode's easy-axis [42,80]. Stray fields can impact the measurement if these two faces are placed too close to or even on top of the transport channel [23,75,76]. 2.)…”
Section: J Magnetic Field Dependent Measurementsmentioning
confidence: 99%
“…However, it has been gradually realized that both these two planar magneto transport effects, namely, the positive LMC and PHE, are not sufficient transport signatures to guarantee the presence of CA in WSMs. Recently, it has been reported that similar planar transport behaviors can also arise through various extrinsic mechanisms [11,[15][16][17][18][19] and even appear in * ygyao@bit.edu.cn materials without any Weyl nodes [20][21][22][23][24][25][26][27][28][29][30][31][32]. In addition, Weyl nodes themselves do not always exhibit positive LMC.…”
Section: Introductionmentioning
confidence: 99%
“…We should mention that an anomalous Hall effect (AHE) ,, and ordinary Hall effect (OHE) can appear as artifacts in the measured SCC signals (Note S3 in the Supporting Information). The anomalous Hall angle obtained by applying an out-of-plane magnetic field to CoFe in our own devices is 1.5%.…”
mentioning
confidence: 99%